Investigating the distinction between Greek and Islamic ontologies; In the philosophical context of Aristotle and Ibn Sina - saeedeh amini; Hamed NAJIESFAHANI (حکمت اسرا, 2019)
Metaphysics or ontology is the most important stream of philosophy, or in other words, the whole stream of philosophy in history. Its two great representatives, Aristotle and Ibn Sina, each had a profound effect on the history of metaphysics. As the founder of metaphysics, Aristotle was able to master the whole course of Greek philosophy for the first time in history and to cover almost all subsequent metaphysical discussions. Therefore, the history of metaphysics must always be written about Aristotle from its beginning to its end. But Ibn Sina's philosophy, unlike Ibn Rushd's, is very different from Aristotle's. Thus, we can speak of two distinct ontologies that were studied in the history of metaphysics from the Middle Ages to Hegel, so that the work of Ibn Sina is more engraved on the history of metaphysics than Aristotle. The present study seeks to pave the way for a fundamental revision of the two philosophers' backgrounds in the re-reading of the history of philosophy, so that the different foundations of their philosophical views can be fully distinguished. The method in question is hermeneutic phenomenology, which seeks to find the foundation of thought in these two different metaphysical developments, although they develop on a single platform, which is metaphysics.